2019
DOI: 10.7150/ijbs.33790
|View full text |Cite
|
Sign up to set email alerts
|

PERK/eIF-2α/CHOP Pathway Dependent ROS Generation Mediates Butein-induced Non-small-cell Lung Cancer Apoptosis and G2/M Phase Arrest

Abstract: Butein, a member of the chalcone family, is a potent anticarcinogen against multiple cancers, but its specific anti-NSCLC mechanism remains unknown. The present study examined the effects of butein treatment on NSCLC cell lines and NSCLC xenografts. Butein markedly decreased NSCLC cell viability; inhibited cell adhesion, migration, invasion, and colony forming ability; and induced cell apoptosis and G2/M phase arrest in NSCLC cells. Moreover, butein significantly inhibited PC-9 xenograft growth. Both in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…CHOP is an important transcription factor involved in regulating apoptosis and drug sensitivity [168][169][170]. Studies have shown that the levels of CHOP mRNA and its protein level were significantly lower in lung cancer tissues compared with noncancerous tissues.…”
Section: Therapeutic Strategies Based On Ncrnas and The Upr In Cancermentioning
confidence: 99%
“…CHOP is an important transcription factor involved in regulating apoptosis and drug sensitivity [168][169][170]. Studies have shown that the levels of CHOP mRNA and its protein level were significantly lower in lung cancer tissues compared with noncancerous tissues.…”
Section: Therapeutic Strategies Based On Ncrnas and The Upr In Cancermentioning
confidence: 99%
“…Further it exerted a dose-dependent effect on focal adhesion kinase, Akt, and ERK phosphorylation in B16F10 cells. In addition, its treatment led to the inhibition of cell adhesion, migration and invasion of NSCLC cells (Di et al, 2019). Zhang et al, (2008) also reported this compound to inhibit the migration as well as invasion of bladder cancer cells by modulating ERK1/2 and NF-kB signaling.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, butein was also reported to exert its antiproliferative and pro-apoptotic effect through inhibition of NF-κB, AP-1 and Akt signaling in HTLV-1infected T cells in both in vitro and in vivo settings clearly indicating its therapeutic potential against adult T-cell leukemia/lymphoma (Ishikawa et al, 2017). Besides, this flavonoid induced apoptosis and arrest at the G2/M phase of cell cycle through PERK/eIF-2α/CHOP pathway dependent ROS generation (Di et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Literatures have demonstrated that butein exposure can increase ROS generation in several tumor cell lines 31‐33 . To further clarify whether p53 was activated through ROS generation in butein‐treated U‐2 OS cells, we first evaluate the level of ROS in these cells using 2′,7′‐dichlorofluorescin diacetate (DCFDA) and MitoSOX Red staining.…”
Section: Resultsmentioning
confidence: 99%
“…Butein inhibits hepatocellular carcinoma growth via the down‐regulation of Aurora B kinase activity 35 . Butein suppresses the cell viability of non‐small cell lung cancer through ER stress‐dependent ROS generation and apoptosis pathway 31 . Butein inhibits cell proliferation and glycolysis in hepatocellular carcinoma through suppressing epidermal growth factor receptor (EGFR) signaling pathway 36 .…”
Section: Discussionmentioning
confidence: 99%